Rapid and mass propagation system for yams (Dioscorea spp.) based on vine cuttings and tissue culture techniques for germplasm collection: onthe job training - Kikuno, H. (International Institute of Tropical Agriculture, 2010)
The production of clean planting materials at the genebank for clonal prppagated crops, such as yam, is essential. The trainee, who came from the National Genebank of Kenya, undertook the training program on vine propagation (VP) tissue culture technique for yam in vitro genebanking from 1 october to December 2010. Since yam is not as popular in East Africa as it is in West Africa, the trainee had to initially gain a general understating of the crop before proceeding with the program. After this training, the expertise would be introduced and used at the National Genebank of Kenya for yam germplasm conservation.